Antibody fluctuations of infected cattle with Fasciola gigantica and the effect of triclabendazole treatment - S Widjajanti; S.E Estuningsih; Suharyanta . (Jurnal Ilmu Ternak dan Veteriner, 2001)
Observation on the antibody fluctuations of infected cattle with metacercariae of Fasciola gigantica and the effect of triclabendazole treatment were made by means of ELISA technique. Seven cattle were infected with 700 metacercariae and one cattle remained uninfected, as negative control animal. Treatment with triclabendazole was given to 6 cattle, when the mean antibody levels of infected cattle reached the peak, and the other one remained untreated, as positive control animal. One week after treatment the mean antibody levels started to drop and then decreased gradually. After eight weeks of treatment, the mean antibody levels of the treated cattle reached the lowest level or the same value as before infection, thereafter, 6 cattle were reinfected with different dosages of metacercariae of F. gigantica. Two cattle were infected with 400 metacercariae, the other two were infected with 600 metacercariae and the rest of them were infected with 800 metacercariae. The results showed that the immunological responses of re-infected cattle are quicker (5 weeks after infection) and the peak of the antibody levels are higher (ELISA OD = 1.7) than after the first infection (11 weeks after infection and ELISA OD = 1.2). However, after re-infection, there were no significant different on the antibody fluctuations and antibody levels among the infected group, although those cattle received different dosages.   Key words: Antibody, cattle, Fasciola gigantica, ELI